Phyto-synthesis, characterization of silver nanoparticles from mint leaf extract and its evaluation in antimicrobial and pharmacological applications - Wasim Akhtar; Muhammad Imran Hamza; Sidra Qayyum; Muhammad Azhar Khan; Naila Mukhtar; Asif Kamal; Rizwan Sarwar; Moona Nazish; Abdulwahed Fahad Alrefae; Mikhlid H. Almutairi; Muhammad Tahir Naseem (BMC Plant Biology)
Abstract Mentha arvensis is an important medicinal herb possess strong therapeutic values, including antioxidant, anti-inflammatory, hepatoprotective, antiulcer, cardioprotective, anticancer, and antimicrobial properties. Also, nanotechnology is an emerging multidisciplinary science having multiple applications in different fields. Based on the medicinal properties of the M. arvensis and applications of the nanoparticles, the current work was focused on the biogenically synthesized AgNPs. The Prepared NPs were characterized via UV–visible spectrometry, Flame Atomic Absorption Spectroscopy (FAAS), X-ray diffraction (XRD) analysis, scanning electron microscopy (SEM), and energy dispersive X-ray spectroscopy (EDX). UV–visible spectral investigation showed an absorption reading peak at 434 nm due to surface plasmon resonance, indicating phyto-reduction. XRD spectrum revealed the crystalline-like nature and average size of AgNPs ranging from 2.5–47.3 nm. SEM micrograph represented the spherical, irregular, and aggregated nature of AgNPs. EDX graph evidenced 68.6% of elemental Ag sample material, hence confirming the phyto-reduction. Biogenically synthesized AgNPs have shown considerable anti-microbial action against gram-negative and positive strains of bacteria. The highest zone of inhibition (ZOI) was detected on higher concentrations of AgNPs towards E. coli, Pseudomonas aeruginosa , Enterobacter aerogenes, and Acetobacter sicerae (14 ± 1.0 mm, 13 ± 2.65 mm, 13 ± 1.0 mm, and 12 ± 1.0 mm, respectively. The excellent antifungal potential against Alternaria alternata, with maximum growth inhibition of 68.1% followed by 65.6% against Aspergillus niger, 64.3% Fusarium oxysporium and 64.1% against Ascochyta rabiei at the highest concentratin of 20 mg was observed. The maximum TAC was 73.5%, TRP 70.2%, DPPH 59.6%, and biocompatibility was 1.66 ± 0.10. Conclusively, the biosynthesized AgNPs have exhibited good potential (therapeutic and antimicrobial properties) and should be further inspected to improve their significance for practical application.